An Orthogonal Investigation in Structures and Performances of Vanadium Modified Li2FeSiO4. (25th October 2017) - Wei, Xuexia; Luo, Xiaoying; Chen, Huizhen; Cheng, Xuan; Huang, Liuying; Zhang, Ying
Abstract : A series of different vanadium modified carbon coated lithium iron silicate (Li2 Fe1-x Vx SiO4 /C) composites were prepared by sol-gel precursor and solid-state reaction using ammonium metavanadate (NH4 VO3 ) as a vanadium source material. The effects of vanadium content, sucrose amount, sol-gel time and type of carboxylate acid on crystal structure, surface morphology, elemental composition and electrochemical performance of Li2 Fe1-x Vx SiO4 /C composites were investigated through orthogonal design experiments. The initial discharge capacity of the nominal 35% vanadium modified Li2 FeSiO4 /C, prepared under the optimized conditions (sucrose amount of 80% and sol-gel time of 2 h using citric acid as a pH regulator), reached as high as 216.7 mAh/g (corresponding to 1.30 moles per formula unit) at 0.1C and room temperature. The composite exhibited a mixed Pmn 21 and P 21 phase with the coexistences of metallic iron (Fe) and lithium silicate (Li2 SiO3 ) as the main impure phases.